Shashi Despande as a Feminist - Sinha, Arti (Journal of Advanced Research in Journalism & Mass Communication, 2020)
Shashi Deshpande, born in 1938 at Dharwad, Karnataka, is the daughter of renowned Kannada dramatist and Sanskrit scholar, Late Adya Rangachar Shriranga. Deshpande, a recipient of the prestigious ‘Sahitya Akademy Award’ for ‘That Long Silence’ is well known for her short stories, children books and novels. Her chief novels include ‘The Dark Holds No Terror’ [1980], ‘The Roots and the Shadows’ [1983], ‘That Long Silence’ [1989], ‘A Matter of Time’ [1996], ‘Small Remedies’ [2000], ‘The Binding Vine’ [2002] etc. In these novels, she has very subtly voiced the agonies, sufferings, hopes, aspirations and frustrations through the protagonists and other characters, who are generally the respresentative of middle class urban educated women. How to cite this article: Sinha A. Shashi Despande as a Feminist. J Adv Res Jrnl Mass Comm 2020; 7(1): 15-16. DOI: https://doi.org/10.24321/2395.3810.202004